Physical Methods for Seed Invigoration: Advantages and Challenges in Seed Technology - Araújo, Susana de Sousa; Paparella, Stefania; Dondi, Daniele; Bentivoglio, Antonio; Carbonera, Daniela; Balestrazzi, Alma (Frontiers in Plant Science, 2016)
In the context of seed technology, the use of physical methods for increasing plant production offers advantages over conventional treatments based on chemical substances. The effects of physical vigourization treatments in seeds can be now addressed at multiple levels, ranging from morpho-structural aspects to changes in gene expression and protein or metabolite accumulation. Among the physical methods available, ”magneto-priming” and irradiation with microwaves or ionizing radiations are the most promissory pre-sowing seed treatments. ”Magneto-priming” is based on the application of magnetic fields and described as an eco-friendly, cheap, non-invasive technique with proved beneficial effects on seed germination, vigour and crop yield. Ionizing radiations, as gamma-rays and X-rays, have been widely regarded as a powerful tool in agricultural sciences and food technology. Gamma-rays delivered at low dose have showed to enhance germination percentage and seedling establishment, acting as an actual ‘priming’ treatment. Different biological effects have been observed in seeds subjected to microwaves and X-rays but knowledge about their impact as seed vigourization agent or stimulatory effects on germination need to be further extended. Ultraviolet (UV) radiations, namely UV-A and UV-C have shown to stimulate positive impacts on seed health, germination and seedling vigour. For all mentioned physical treatments, extensive fundamental and applied research is still needed to define the optimal dose, exposition time, genotype- and environment-dependent irradiation conditions. Electron paramagnetic resonance (EPR) has an enormous potential in seed technology not fully explored to monitor seed vigourization treatments and/or identifying the best suitable irradiation dose or time-point to stop the treatment. The present manuscript describes the use of physical methods for seed vigourization, while providing a critical discussion on the constraints and advantages. The future perspectives related to the use of these approaches to address the need of seed technologists, producers and trade markers will be also highlighted.